Relationship between immunohistochemical markers and clinical pathological variables in clear cell renal cell carcinoma - Liu, Pengshuai; Wei, Junli; Chen, Shubo (Frontiers in Oncology, 2025)
ObjectiveTo explore the factors associated with the immunohistochemical results in clear cell renal cell carcinoma (ccRCC).MethodsThis retrospective, single-center observational study included patients with pathologically confirmed ccRCC who underwent nephrectomy at Xingtai People’s Hospital between January 2023 and October 2024. Logistic and linear regression was used to evaluate predictors of ccRCC features, with adjustments for demographic and clinical factors.ResultAmong the 50 patients (median age, 66 years; 64% male), high Vimentin expression was significantly associated with vascular invasion (adjusted OR, 2.90; 95% CI, 1.05–7.62; P = 0.031), lymph node metastasis (OR, 2.62; 95% CI, 1.03–8.12; P = 0.042), distant metastasis (OR, 3.10; 95% CI, 1.01–12.54; P = 0.048), and larger tumor size (P = 0.004). Ki−67 expression varied significantly by alcohol consumption (P = 0.024), perineural invasion (P = 0.038), and was positively correlated with serum creatinine (P = 0.017). CD10 expression was inversely correlated with bilirubin levels (P = 0.021) but not associated with invasive or metastatic features.ConclusionVimentin expression was strongly associated with markers of tumor invasiveness and may serve as a practical prognostic biomarker in ccRCC. Ki-67 may reflect proliferative activity and systemic burden. CD10 remains diagnostically useful but lacks prognostic value. Incorporating these IHC markers into routine pathology assessment may enhance risk stratification and inform individualized management of ccRCC with more exploration and validation.